Identification of novel genetic variants and in-silico pathway analysis in patients with dilated cardiomyopathy / Rafezah Razali - Razali, Rafezah (2019)
Dilated cardiomyopathy (DCM), a genetically heterogeneous heart muscle disease is the third leading cause of heart failure. DCM usually leads to severe congestive heart failure and an increased risk of sudden cardiac death. The limitations of heart donor and transplant complications necessitate the development of new treatment strategies targeting the molecular mechanisms involving the cardiomyocytes. Identification of genetic variants and its molecular pathways may be useful in providing mechanistic insights in DCM and its progression to heart failure. More need be known about genetics of DCM especially among patients in South East Asia including Malaysia. This study attempted to identify the underlying genetic variants that may lead to DCM by utilizing the whole exome sequencing. The study also explores the presence of the identified genetic variants among the family members of DCM patients and to investigate the role of the identified genes involved in the pathogenesis of DCM among Malaysian patients using in-silico analyses. 1982 subjects were screened from various community health screening programs (1978 males; 33 females); and 29 from hospital admissions (26 males; 3 females) were recruited. One subject from the community screening was diagnosed as DCM, thus giving the estimated prevalence of DCM in the current study as 0.5%. This prevalence finding serves as a first report of DCM prevalence in Malaysia. 111 first degree family members of the DCM patients were also recruited for Sanger sequencing to determine if the genetic variants found in DCM patients were also present among the family members. The genetic variants from exome sequencing data were compared with publicly available reference databases. The variants were subsequently annotated using the annotation tools in order to predict whether an amino acid substitution effects were damaging (the variants affect protein function and structure). 223 novel damaging variants and 114 non-synonymous TTN variants were identified in the DCM patients. 62 nonsynonymous TTN variants (54.4%) identified in 83% of DCM patients have minor allele frequency of less than 1% and thus were classified as TTN rare variants. The novel damaging variants were not found among the family members of DCM patients suggesting the lack of familial involvement in these DCM patients. The genes underlying the novel damaging variants when performed David Pathway analysis were significantly enriched in the Krueppel-associated box (KRAB) domain binding (Benjamini corrected p=0.00004), myosin complex (Benjamini corrected p=0.004), calcium-mediated signaling (Benjamini corrected p=0.005) and cytoskeleton (Benjamini corrected p=0.008) pathways. In the present study, novel candidate genes for DCM have been identified, including Myosin light chain 2 (MYL2), Myosin light chain 7 (MYL7), Kruppel-associated box domain (KRAB) Zinc-fingers gene family, zinc finger MYM-type containing 4 (ZMYM4), Interleukin 23 receptor (IL23R), F-box protein 22 (FBX022), phospolipase C gamma 1 (PLCG1), Ryanodine receptor 1 (RYR1), Integrin beta 7 (ITGB7) and GNAS complex locus (GNAS) genes that involve in the sarcomere assembly in providing structural integrity of cardiomyocytes, autoimmune and inflammatory response, calcium signalling and regulation of actin cytoskeletal pathways. In addition, there are 21 recurrent variants that were observed to have unknown effect in DCM pathogenesis, hence classified as variants of uncertain significance (VUS). These imply that DCM is genetically heterogeneous disease that involves the activation of multiple signalling pathways. This study serves as first report on the genetic of DCM in Malaysia and South East Asia countries.